2019
DOI: 10.1101/643114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unique and redundant roles of SOX2 and SOX17 in regulating the germ cell tumour fate

Abstract: Embryonal carcinomas (ECs) and seminomas are testicular germ cell tumours. ECs display expression of SOX2, while seminomas display expression of SOX17. In somatic differentiation, SOX17 drives endodermal cell fate. However, seminomas lack expression of endoderm markers, but show features of pluripotency. Here, we use ChIP-sequencing to report and compare the binding pattern of SOX17 in seminoma-like TCam-2 cells to SOX2 in EC-like 2102EP cells and SOX17 in somatic cells. In seminoma-like cells, SOX17 was detec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Jostes et al. [ 45 ] finally illuminated the different roles of SOX2 and SOX17 in TGCT fate. ChIP-seq data revealed that in TCam-2 cells, SOX17 also bound to both motifs (canonical and compressed), resulting in an overlap of SOX2 and SOX17 target genes.…”
Section: Sox2 and Sox17 Regulating Tgct Fatementioning
confidence: 99%
See 4 more Smart Citations
“…Jostes et al. [ 45 ] finally illuminated the different roles of SOX2 and SOX17 in TGCT fate. ChIP-seq data revealed that in TCam-2 cells, SOX17 also bound to both motifs (canonical and compressed), resulting in an overlap of SOX2 and SOX17 target genes.…”
Section: Sox2 and Sox17 Regulating Tgct Fatementioning
confidence: 99%
“…Therefore, pluripotency factors can be regulated by SOX17 as well as SOX2, indicating an overlap in their function as transcriptional regulators ( Table 1 ). However, SOX2 also binds to genes upregulated in embryonic stem cells like GDF3, LEFTY2, SALL4, TP53, as well as SOX2 and OCT4 itself, creating a regulating loop, which was not found for SOX17 binding sites [ 45 ]. Further, comparing SOX17 binding sites in TCam-2 and differentiated ESC, only showed an overlap of 10%, where, out of all genes bound by SOX17 in TCam-2, 66% were only in TCam-2, but not found in the somatic lineages.…”
Section: Sox2 and Sox17 Regulating Tgct Fatementioning
confidence: 99%
See 3 more Smart Citations